Case report: PIK3CA somatic mutation leading to Klippel Trenaunay Syndrome and multiple tumors - Serio, Viola Bianca; Palmieri, Maria; Innamorato, Simona; Loberti, Lorenzo; Fallerini, Chiara; Ariani, Francesca; Antolini, Enrica; Covarelli, Jasmine; Vaghi, Massimo; Frullanti, Elisa; Renieri, Alessandra; Pinto, Anna Maria (Frontiers in Genetics, 2023)
We report a case of Klippel Trenaunay Syndrome (KTS) that was monitored both clinically and molecularly over a period of nine years. A somatic mosaic mutation of PIK3CA (p.(E545G)) was identified using both cfDNA NGS liquid biopsy and tissue biopsy. At the age of 56, due to intervening clonal mutations in PIK3CA background, she developed a squamous cell carcinoma in the right affected leg which was treated surgically. Nine years later, lung bilateral adenocarcinoma arose on PIK3CA mutated tissues supported by different clonal mutations. One year later, the patient died from metastases led by a new FGFR3 clone unresponsive to standard-of-care, immunotherapybased. Our results highlight the presence of a molecular hallmark underlying neoplastic transformation that occurs upon an angiodysplastic process and support the view that PIK3CA mutated tissues must be treated as precancerous lesions. Importantly, they remark the effectiveness of combining cfDNA NGS liquid and tissue biopsies to monitor disease evolution as well as to identify aggressive clones targetable by tailored therapy, which is more efficient than conventional protocols. 1 ha formattato: Italiano (Italia) ha formattato: Italiano (Italia) ha formattato: Italiano (Italia) ha formattato: Tipo di carattere: Grassetto